Sosialisasi Legalitas Badan Usaha dan Pendaftaran Merek Dagang Dalam Upaya Meningkatkan Penjualan Produk UMKM di Wilayah Banyumas - Maya Ruhtiani; Yuris Tri Naili; Faizal Rizky Yuttama (Pusat Riset dan Inovasi Nasional, 2024)
This article evaluates the effectiveness of the socialization of business entity legality and trademark registration to increase sales of MSME products in the Banyumas region. The main problems MSMEs face in Banyumas are the low level of business legality and the need for awareness of the importance of trademark registration, which impacts low consumer confidence and limited market access. The research method used was qualitative, with data collection techniques through observation and documentary studies. The results showed that the socialization of MSME actors in business legality and trademark registration increased the knowledge and awareness of MSME actors about the importance of business legality and trademarks. The dynamics of the mentoring process showed the strengthening of MSME networks and collaboration and the emergence of local leaders who play an active role in the community.